A survey on perception of teachers, parents and students in learning songs with explicit lyrics / Jeanie Ling Ching - Jeanie Ling , Ching (2018)
The objective and purpose of this research study is to investigate the perception, views, opinion of attitudes, behaviour and acceptance of teachers, parents and students’ in learning songs with explicit lyrics. The awareness towards learning songs with explicit lyrics is based on age, gender, familiarity, musical training and preferences of 17 teachers, 12 parents and 122 students from selected music schools and music colleges in Ampang and Kuala Lumpur, Malaysia. Problems occurs when teenagers enjoy listening and singing songs with explicit lyrics. Their attitudes and behaviour were influenced and affected by the music they listen to and utterances of vulgar words. This created awareness and perception of all three correlated group of respondents: teachers, parents and students in teaching, listening, learning and singing songs with explicit lyrics in the class. Using self-report survey questionnaires and interviews, data were collected from Teachers (20-55 years old), Parents (35-61 years old) and students of teenagers (13-18 years old) and youth (19-25 years old). Researcher use Likert scale to measure the dependable variables n= 122 and mean scores; focused into the awareness, familiarity, preferences and perception towards learning of songs with explicit lyrics. From the research findings, the teachers take full control of the class with effective teaching styles and learning strategies. Teachers are wise in choosing songs and modify lyrics if teaching songs with explicit lyrics. Parents trust the teacher’s responsibility to teach and guide their children regardless of learning songs with explicit lyrics, as long as it promotes their children’s interest in music. Students enjoy and have fun singing to the rhythmic hip-hop and rap songs, regardless of the explicit lyrics. Future research may explore into the correlation between the three respondents to improve into a more effective, enjoyable and fun learning, by integrating hip-hop based education as a curriculum. The implementation of hip-hop into the curriculum promotes cultural relevance to youth, and deeper learning through relevance of the learning process.